Angiotensin Type 2 Receptors: Painful, or Not? - Pulakat, Lakshmi; Sumners, Colin (Frontiers in Pharmacology, 2020)
.Pain in response to various types of acute injury can be a protective stimulus to prevent the organism from using the injured part and allow tissue repair and healing. On the other hand, neuropathic pain, defined as ‘pain caused by a lesion or disease of the somatosensory nervous system’, is a debilitating pathology. The TRPA1 neurons in the Dorsal Root Ganglion (DRG) respond to reactive oxygen species (ROS) and induce pain. In acute nerve injury and inflammation, macrophages infiltrating the site of injury undergo an oxidative burst, and generate ROS that promote tissue repair and induce pain via TRPA1. The latter discourages using the injured limb, with a lack of movement helping wound healing. In chronic inflammation caused by diabetes, cancer etc., ROS levels increase systemically and modulate TRPA1 neuronal functions and cause debilitating neuropathic pain. It is important to distinguish between drug targets that elicit protective versus debilitating pain when developing effective drugs for neuropathic pain. In this context, the connection of the Angiotensin type 2 receptor (AT2R) to neuropathic pain presents an interesting dilemma. Several lines of evidence show that AT2R activation promotes anti-inflammatory and anti-nociceptive signaling, tissue repair, and suppresses ROS in chronic inflammatory models. Conversely, some studies suggest that AT2R antagonists are anti-nociceptive and therefore AT2R is a drug target for neuropathic pain. However, AT2R expression in nociceptive neurons is lacking, indicating that neuronal AT2R is not involved in neuropathic pain. It is also important to consider that Novartis terminated their phase II clinical trial (EMPHENE) to validate that AT2R antagonist EMA401 mitigates post-herpetic neuralgia. This trial, conducted in Australia, United Kingdom, and a number of European and Asian countries in 2019, was discontinued due to pre-clinical drug toxicity data. Moreover, early data from the trial did not show statistically significant positive outcomes. These facts suggest that AT2R may not be the proper drug target for neuropathic pain in humans and its inhibition can be harmful.